Diversity of rhizobia and carbon sequestration in soils under coffee cropping systems and Mata Atlantica biome - Nunez Villalobos, Ana Lúcia (2022)
Coffee is one of the most consumed beverages in the world, making it a global commodity being the main product for export to Minas Gerais and finding plantations in all biomes, replacing or adjacent to natural vegetation. Microorganisms are relevant components of biodiversity promoting plant growth through processes such as biological nitrogen fixation. Considering the importance of rhizobia, the main objective of this work was to study, via cultural characteristics, the biodiversity of nitrogen-fixing bacteria considering the physical and chemical attributes of the soil, as well as carbon sequestration in coffee areas and Atlantic Forest biome. For this, the diversity of isolated rhizobia was evaluated using species of bait plants. The study was carried out in six areas: in each area samples of the first 10 cm of soil were collected in five-point transepts with five meters of separation. The bait plants Macroptilium atropurpureum and Vigna unguiculata were grown in bottles under axenic conditions, with Hoagland solution as a source of nutrition and inoculated with a dilution of the collected soils. Therefore, the presence of nodules and their weight, root weight, SPAD index and dry matter weight were determined. After disinfection, the nodules were macerated in Petri dishes with YMA medium and the colonies that appeared were isolated until reaching the pure strains for logos to characterize and group them. It is concluded that soils under coffee areas have a diverse community of rhizobia. The Atlantic Forest biome presented higher density and diversity of rhizobia when compared to coffee monoculture areas, also having higher total carbon content. There is a relationship between rhizobia density and soil chemical attributes such as pH and copper content. The bait plant Vigna unguiculata was better to capture rhizobia in the studied areas and they were highly variable in terms of physical and chemical attributes. Finally, it can be concluded that the nitrogen fixing bacteria found are highly resilient, since the physical and chemical characteristics and carbon content were very variable and yet, they managed to nodule effectively.